2021
DOI: 10.1007/s00217-021-03883-y
|View full text |Cite
|
Sign up to set email alerts
|

Emulsifying properties of lentil protein preparations obtained by dry fractionation

Abstract: Dry fractionated legume protein ingredients are gaining attention as alternatives to conventional solvent extracted legume proteins, being more resource efficient and often exhibiting novel functional properties. However, lack of knowledge about the relationship between composition and functionality limit a more wide-spread use of dry-fractionated legume protein in applications. In this study, lentil fractions of different degrees of refinement were prepared using air classification having protein and starch c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
1
2
0
5
Order By: Relevance
“…Therefore, finer particle size can enhance the emulsifying properties. Funke et al 33,34 . suggested that dry‐fractionated lentil protein has a good potential in stabilizing an emulsion, corroborating the findings of Tabtabaei et al ., 10 who revealed a similar emulsifying ability comparing navy bean dry‐fractionated protein and commercial soy protein concentrate, and better foaming stability compared to the soy.…”
Section: Functional Properties Of Dry‐fractionated Proteinssupporting
confidence: 55%
“…Therefore, finer particle size can enhance the emulsifying properties. Funke et al 33,34 . suggested that dry‐fractionated lentil protein has a good potential in stabilizing an emulsion, corroborating the findings of Tabtabaei et al ., 10 who revealed a similar emulsifying ability comparing navy bean dry‐fractionated protein and commercial soy protein concentrate, and better foaming stability compared to the soy.…”
Section: Functional Properties Of Dry‐fractionated Proteinssupporting
confidence: 55%
“…Furthermore, air classification can help maintain the native functionality of proteins without the addition of chemical reagents (Schutyser et al., 2015). For instance, better solubility, foam stability, ESI, and lower viscosity reflected native techno‐functional properties compared to traditional protein isolates (Funke et al., 2022; Pelgrom et al., 2014). Although dry‐separating MBPs yield relatively lower purity than wet separation, it is expected that most foods do not require high purity (Schutyser et al., 2015).…”
Section: Extraction Methods and Ingredients Characteristics Of Mbpmentioning
confidence: 99%
“…При этом небелковые компоненты отделяются от белоксодержащей фракции. Для классификации измельченного сырья чаще всего используют центробежные воздушные классификаторы [9], а также рассев на ситах и электросепарацию [10]. Подбирая параметры процесса классификации, который проводят в одну или в две стадии, получают белковые продукты различного состава.…”
Section: Introductionunclassified
“…При фракционировании бобов наиболее полное отделение белка выявлено для твердых семян, а при фракционировании пшеницы -для мягких семян [5]. В работе [7] показано, что уровень сырого протеина мало влияет на эффективность фракционирования, а в исследовании [9] выявлена положительная корреляция между содержанием сырого протеина в горохе и его количеством в мелкой фракции. Содержание сырой клетчатки неоднозначно влияет на эффективность фракционирования, так как зависит от состава клеточной стенки (количество нейтрально-детергентной клетчатки) и ее толщины.…”
Section: Introductionunclassified